Balance of Payments Crises Under Inflation Targeting - Li, Shujing (IMF Working Papers; Working Paper ;, 2007)
This paper analyzes a small open economy model under inflation targeting. It shows why such a monetary regime is vulnerable to speculative attacks that take place over a short period rather than instantaneously. The speed at which the regime collapses, and the extent of reserve losses, are increasing in the central bank's explicit or implicit commitment to intervene in the foreign exchange market. Attacks are therefore ranked, from most to least severe, as follows: Exchange rate targeting, CPI inflation targeting, domestic nontradables inflation targeting, and money targeting. Under inflation targeting the size of the attack is increasing in the tradables consumption share.